CO2 conversion to syngas via electrification of endothermal reactors: Process design and environmental impact analysis. (1st August 2022) - Cao, Guoqiang; Handler, Robert M.; Luyben, William L.; Xiao, Yue; Chen, Chien-Hua; Baltrusaitis, Jonas
Graphical abstract: Highlights: SMR + rWGS to produce syngas process design was performed. Emerging ohmic (resistive) heating was adopted to replace fuel heated furnace. SMR electrification is the key for the overall GHG emission reductions. Wind electricity use improved electrification design environmental impacts. Abstract: CO2 utilization via reverse water gas shift (rWGS) reaction has been proposed as a path to the sustainable utilization. This work presents a detailed process modelling study where steam methane reforming (SMR) generated hydrogen was combined with rWGS to produce syngas (CO + H2 ) with various hydrogen-to-carbon oxide ratios. To further decrease CO2 emissions that may offset the benefits of CO2 converted in rWGS, electrification of endothermal reactors, both SMR and rWGS was considered where CO2 emitting fuel burning in the furnace was replaced by the emerging ohmic (resistive) heating. Material and energy inventory obtained from process design calculations was used to perform Life Cycle Analysis (LCA) to calculate environmental impacts of CO2 consumption and reactor electrification. The results showed that greenhouse gas emissions, in CO2 kg equivalent, were the lowest when both SMR and rWGS were heated using wind-generated electricity, decreasing from 25 to 10 kg CO2 equivalent for H2 :CO = 2:1 while the conventional electricity mix used for furnace electrical heating across the board of scenarios generated highest environmental impacts, much higher than those that used natural gas as fuel. Process economics calculations suggested that, when both SMR and rWGS were electrically heated, the process only showed product syngas cost parity with the conventional fuel heated design when electricity cost was ∼$0.008/kWh. This suggests that CO2 utilization scenarios involving process electrification need to be carefully considered from the total design perspective so they do not produce more greenhouse gases than in conventional non-electrified scenarios.